The Development of the Mulok Curriculum of the Manggarai Traditional Rite as a Preservation of Manggarai Culture at the Elementary Levels - Kurniawati, Yuliana (Budapest International Research and Critics University, 2021)
This study is aims to examines the existence of the curriculum as a medium or vehicle for dynamic learning so that it must be developed and assessed regularly and continuously following developments in the student learning environment and based on regional or regional characteristics. Regional culture is the foundation of Indonesia's national culture. Loving and studying regional culture is a manifestation of loving the national culture (Indonesia). In the current global era, efforts to strengthen the nation's character are carried out by applying the values of local wisdom. To improve students' ability to think critically, increase self-confidence, instill moral values and master learning materials. Based on the results of the researchers' initial analysis, towards the potential of the Manggarai traditional rites, several factors are supporting this traditional rite that can be arranged in a form The local content curriculum includes: (1) Customary rites that are inherent in the daily lives of the Manggarai people and are passed down from generation to generation. (2) Customary rites are cultural heritage in the form of habits, and these habits can be used as a source of learning. (3) Manggarai language is the mother tongue of the Manggarai-Flores people of NTT which is used in their daily life, including their traditional rituals. When these traditional rites are included in the local curriculum, it is also a real effort to preserve Manggarai customs. (4) Cultural arts.